Implementasi Sensor RFID dan Sel Fotovoltaik sebagai Penerangan Jalan Hemat Energi di Desa Ciramahilir Kabupaten Purwakarta - Epa Rosidah Apipah; Dani Usman; Yoga Amundiasmo; Hasan Hasan; Jejen Supriadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Ciramahilir Village in Purwakarta Regency faces a serious problem due to the lack of street lighting, which negatively impacts the safety, comfort, and socio-economic activities of the community. This community service program aimed to improve the quality of life for residents by installing solar-powered street lights at strategic locations within the village. The approach used was Participatory Action Research (PAR), involving the community actively in every stage of the program—from problem identification and planning to implementation and evaluation. The results show that the street lighting intervention had a positive impact on residents' sense of security, increased night-time activities, and strengthened collective awareness to maintain public infrastructure. Additionally, technical training and assistance enhanced the community's capacity to sustain the installed systems. This activity also demonstrated that appropriate renewable energy technology can serve as an effective tool for promoting sustainable social change in rural areas.